2013
DOI: 10.1371/journal.pone.0076992
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Cardiac Renin Angiotensin System in Oophorectomized and Estrogen-Replete mRen2.Lewis Rats

Abstract: The cardioprotective effects of estrogen are well recognized, but the mechanisms remain poorly understood. Accumulating evidence suggests that the local cardiac renin-angiotensin system (RAS) is involved in the development and progression of cardiac hypertrophy, remodeling, and heart failure. Estrogen attenuates the effects of an activated circulating RAS; however, its role in regulating the cardiac RAS is unclear. Bilateral oophorectomy (OVX; n = 17) or sham-operation (Sham; n = 13) was performed in 4-week-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 81 publications
4
51
2
1
Order By: Relevance
“…Immunohistochemical staining of formalin-fixed and paraffin-embedded heart sections was performed as we described before [10,11,13,15]. Tissue sections were incubated with antibodies against chymase (1:1000, Bioss, Inc.) or Ang II (1:2000, IgG Corp, Nashville, TN, USA) overnight at 4°C, rinsed with PBS, and incubated with biotinylated secondary IgG (Vector Laboratories, Burlingame, CA) for 3 hours at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Immunohistochemical staining of formalin-fixed and paraffin-embedded heart sections was performed as we described before [10,11,13,15]. Tissue sections were incubated with antibodies against chymase (1:1000, Bioss, Inc.) or Ang II (1:2000, IgG Corp, Nashville, TN, USA) overnight at 4°C, rinsed with PBS, and incubated with biotinylated secondary IgG (Vector Laboratories, Burlingame, CA) for 3 hours at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Mounting evidence indicates that estrogen regulates all components of the renin-angiotensin-system (RAS) [2,12,13]. In the OVX mRen2.Lewis rat, an established rodent model that mimics the cardiac phenotype of women following surgical or natural cessation of ovarian hormone production, estrogen replacement reduces plasma levels of angiotensin (Ang) II and increases circulating Ang-(1-7), as well as corrects the increase in circulating activities of renin and angiotensin-converting enzyme (ACE) [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 Estrogens also stimulate renin release from the juxtaglomerular cells through estrogen receptor-α (ERα), 30 whereas endogenous estrogens exert inhibitory effects on the RAAS. 28,29 Experimental studies have shown that circulating levels of aldosterone increase after menopause and that estrogen therapy blunts this increase [31][32][33][34][35] ; however, corresponding data in humans are lacking.…”
Section: Estrogens and The Raasmentioning
confidence: 99%